Case report: Four cases of kidney disease in Giant African Land Snails (Lissachatina fulica) - Schmidt-Ukaj, Silvana; Gumpenberger, Michaela; Mutschmann, Frank; Richter, Barbara (Frontiers in Veterinary Science, 2023)
Giant African Land Snails like Lissachatina fulica have become increasingly popular as pets in Europe, but little is known yet about land snail diseases and their therapy. These case reports show the history of four adult Lissachatina fulica with apathy and esophagus protrusion or prolapse in three cases and edema and mantle collapse in another case. Renomegaly and/or kidney deposits could be demonstrated in radiographic and/or CT examinations in all four cases. Necropsy and histology revealing nephropathy could be performed in three cases. With these first case reports on land snails with kidney disease, we hope to encourage diagnostic imaging and further veterinary research in land snails to improve our knowledge about their diseases.